An experimental investigation of the impact response and Post-impact shear buckling behaviour of hybrid composite laminates. (1st February 2023) - Damghani, Mahdi; Saddler, John; Sammon, Ethan; Atkinson, Gary A.; Matthews, Jason; Murphy, Adrian
Highlights: Hybrid laminates endured less damage after impact compared to non-hybrid laminates. Novel machine vision techniques located the damage on non-hybrid laminates. Both laminate types showed stable buckling and post-buckling path after impact. Hybrid laminates had higher buckling load than non-hybrid laminates after impact. Abstract: This paper investigates the effect of transverse impact loading on the in-plane shear behaviour of two laminate configurations. The extensive experimental studies consider a pure carbon laminate (type 1) and a novel X-shaped carbon/glass laminate (type 2). The results establish that all three graduated impact energy levels (5J, 7.5J and 10J) induce through-thickness matrix cracking, fibre breakage and delamination in the type 1 laminate. However, the use of glass plies in the type 2 laminates resulted in only matrix cracking towards the impacted surface and limited through-thickness damage. Post impact, both laminate types demonstrated lower buckling load, failure load and stiffness. The reduction in buckling load of the type 1 specimens was greater than that of the type 2 specimens. However, the reduction in failure load of the type 1 specimens was less than that seen in the type 2 specimens. Both laminate types demonstrated a stable post-buckling equilibrium path. A novel machine vision technique based on polarisation imaging was successful in standardising the process of identifying the damage location/size for the type 1 laminates, but not for the type 2 laminates. This was due to the inclusion of surface glass plies which, unlike carbon plies, do not polarise light at the point of reflection.